Ecoliteracy and Environmental Fiqh in Pesantren : Transforming Awareness for Sustainability (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2025)
This study aims to conceptually examine and formulate the integration of ecoliteracy and environmental fiqh as a theoretical foundation for transforming students’ awareness toward sustainability within pesantren. Employing a qualitative library research approach with comparative content analysis, the study reviews key literature on the dimensions of ecoliteracy, principles of environmental fiqh grounded in ḥifẓ al-bi’ah and the concept of amanah, as well as empirical findings from studies on Green Pesantren practices in Indonesia. The findings indicate that ecoliteracy provides a scientific and methodological framework for understanding ecological systems and developing practical ecological skills, while environmental fiqh functions as a normative foundation and a source of theological motivation that strengthens the internalization of environmental values among santri. The integration of these approaches results in an Ecological–Theological Awareness Transformation Model that explains the transformation of ecological awareness through cognitive, affective, and conative dimensions, thereby fostering sustainable behavior rooted not merely in structural compliance but in moral and spiritual consciousness. The primary contribution of this study lies in articulating the concept of a Sustainable Green Pesantren that harmonizes ecological science with Islamic spiritual values as a foundation for sustainable environmental education in pesantren.